Visual Identity Menara Gentala Arasy Di Kota Jambi - Ardi Chandra; Zubaidah Zubaidah (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
Gentala Arasy Tower is an Islamic architecture that implies the development of Islam in Jambi Province and is known as an icon or marker of the capital. However, behind the existence of this tower does not yet have a Visual Identity or Logo. The advantage of this tower is as a religious cultural attraction as well as there is a museum and theater underneath. Based on the information provided, the purpose of the design is to create a new brand image to local and non-local communities and increase the brand awareness of the community towards the icon of this capital city. The design method used is ADDIE modification theory, which consists of five stages, specifically analysis, developing brand identity, design process, implementation, and evaluation. This method is suitable because it is easy to learn, simple, and systematic. In addition, this method is also known to have five components that are interrelated with each other and can not be set randomly thus that it can be easily understood by the audience. In the troubleshooting process, an AIDA (Attention, Interest, Desire, Action) is the used to help find a solution to an existing problem. In data collection, observations, interviews, documentation, and literature are conducted. Thus, the results of Visual Identity design will be applied to the Graphic Standard Manual (GSM) as the main media and there are several other supporting media such as, motion design, poster, neon box, merchandise (t-shirts, hats, bags, keychains), stationery sets (map holders, letterheads, name cards, stamps).Kata kunci: visual identity, gentala arasy tower, graphic standard manual